2011
DOI: 10.1128/jvi.02359-10
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of Major Nonessential Genomic Regions in the Vaccinia Virus Lister Strain Enhances Attenuation without Altering Vaccine Efficacy in Mice

Abstract: The vaccinia virus (VACV) Lister strain was one of the vaccine strains that enabled smallpox eradication. Although the strain is most often harmless, there have been numerous incidents of mild to life-threatening accidents with this strain and others. In an attempt to further attenuate the Lister strain, we investigated the role of 5 genomic regions known to be deleted in the modified VACV Ankara (MVA) genome in virulence in immunodeficient mice, immunogenicity in immunocompetent mice, and vaccine efficacy in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 74 publications
0
17
0
Order By: Relevance
“…7A ). To investigate the requirement for CD8 T cell immunity during a less virulent VACV infection we utilized two live-attenuated VACV variants that differ in their expression of several virulence factors that determine their replicative capacity and virulence in mice (37, 38). This reduced virulence is revealed by the need to utilize a significantly higher infectious dose (2 × 10 6 PFU/mouse) to provoke a measurable immune response and the lack of significant weight loss or outward signs of illness throughout infection.…”
Section: Resultsmentioning
confidence: 99%
“…7A ). To investigate the requirement for CD8 T cell immunity during a less virulent VACV infection we utilized two live-attenuated VACV variants that differ in their expression of several virulence factors that determine their replicative capacity and virulence in mice (37, 38). This reduced virulence is revealed by the need to utilize a significantly higher infectious dose (2 × 10 6 PFU/mouse) to provoke a measurable immune response and the lack of significant weight loss or outward signs of illness throughout infection.…”
Section: Resultsmentioning
confidence: 99%
“…Experimental deletion of individual and multiple genes in OPXV genomes has been used to study virulence factors as well as to improve the immunogenicity and safety of vaccine vectors (Dimier et al, 2011; Johnston and McFadden, 2004; Kochneva et al, 2005). These studies have shown that deletion of individual genes can either reduce (Johnston and McFadden, 2004; Senkevich et al, 1994) or enhance (Estep et al, 2011; Ng et al., 2001) replication and virulence.…”
Section: Discussionmentioning
confidence: 99%
“…Over the course of the passages, six major deletions of 2.7 to 6.5 kbp and a large number of smaller deletions, insertions, and point mutations occurred in the genome (34). We and others have recently demonstrated that, in contrast to general belief, introduction of the six major deletions was not sufficient to create a severely host-range-restricted VACV with MVA-like properties (13,35). Host range restriction of MVA must therefore be governed by additional or completely independent mutations.…”
mentioning
confidence: 89%
“…The samples were incubated with the DNase for 30 min at 37°C, and the DNase was subsequently inactivated by addition of 1.24 l of 0.5 M EDTA (pH 8.0) and heating to 75°C for 10 min. Reverse transcription was performed using an Omniscript reverse transcriptase (RT) kit (Qiagen) in the presence of RNase inhibitor (human; Sigma-Aldrich) at a final concentration of 10 U/l for 90 min at 37°C using oligo(dT) [12][13][14][15][16][17][18] primers (Invitrogen). A 1-l volume of RT reaction mixture was added to 20 l of the total PCR mixture for real-time quantitative PCR (qPCR).…”
Section: Cells and Virusesmentioning
confidence: 99%